Religion: A Vehicle for Crisis, Peaceful Co-Existence and Stability in Nigeria - Sibani, Clifford Meesua (KWASU Journal of Religious Studies, 2018)
Religion is a fundamental aspect of human existence. Religion is the belief in the super abundant reality who oversees the affairs of human beings and the cosmic environment. Obviously, religion has created serious problems in Nigerian nation via religious intolerance from religious fanatics which has led to the devastation of so many lives and property. However, irrespective of the problems caused by religion in Nigeria, the building of peace bridges for peaceful coexistence and stability and as well standing as a watch dog for good moral conduct in the polity of the nation. This research gives a historical exposition of religious crisis in Nigeria, the value of religion, how religion is maintaining peaceful co-existence and religious dialogue as a means for peace and stability in Nigeria. This research made use of historical method as books and journals were consulted.